A pilot-scale study on the treatment of landfill leachate by a composite biological system under low dissolved oxygen conditions: Performance and microbial community. (January 2020) - Song, Jianyang; Zhang, Wei; Gao, Junfeng; Hu, Xiaoling; Zhang, Chenlu; He, Qiulai; Yang, Fei; Wang, Hongyu; Wang, Xueyu; Zhan, Xiang
Graphical abstract: Highlights: This system showed good performance for landfill leachate treatment in pilot-scale. This system had a strong ability to resist impact load. This system could significantly improve the biodegradability of leachate. This system was beneficial for the enrichment of denitrifying bacteria. Abstract: In this work, a pilot-scale low dissolved oxygen (DO) composite biological system (LDOCBS) composed of an anoxic rotating biological contactor (RBC) and four aeration tanks with gradient aeration was used to treat landfill leachate for 88 d. The maximum removals of 85.65%, 99.92% and 84.06% for chemical oxygen demand (COD), ammonia (NH4 + -N) and total nitrogen (TN) were achieved, respectively. The three-dimensional exaction and emission matrix (3D-EEM) fluorescence spectroscopy revealed that the biodegradability of leachate was significantly improved by the LDOCBS. Mass balance calculations showed that the COD removal and denitrification process mainly occurred in RBC while 1# contributed primarily to nitrification. High-throughput sequencing analysis indicated that denitrifying bacteria with highly relative abundances of 46.45%–53.81% played key roles in organic degradation and nitrogen removal. This work could add some guiding insights into the cost-efficient treatment of landfill leachate by the composite biological system.